Adherence to intermittent preventive treatment for malaria in pregnancy in urban Kano, Northern Nigeria - Iliyasu, Z.; Aliyu, M.H.; Jibo, A.M.; Baba, A.S.; Abubakar, I.S.; Galadanci, H.S.; Gajida, A.U. (2012)
Malaria in pregnancy is associated with substantial risk of maternal and fetal morbidity and mortality. The uptake of preventive antimalarials is low in malaria endemic countries, including Nigeria. Using a cross-sectional study design, we assessed factors associated with uptake and adherence to intermittent preventive treatment for malaria in pregnancy (IPTp) among antenatal attendees in primary health centers in Kano, northern Nigeria (n=239). A total of 137 respondents (57.3%) reported receiving preventive antimalarials, but only 88 respondents (36.8%) [95% confidence interval (CI): 30.7-43.3%] reported ingesting pills in the clinic under supervision. Factors associated with adherence to IPTp after adjustment for potential confounding included: advanced maternal age [adjusted odds ratio (AOR) (95%CI) = 2.1 (1.3-6.37)], higher educational attainment [AOR (95%CI) = 3.2 (1.32-6.72)], higher parity [AOR (95%CI) = 1.6 (1.07-3.94)], lower gestational age at booking [AOR (95% CI) = 1.72 (1.24-3.91)], and use of insecticide-treated nets [AOR (95%CI) = 2.03 (1.13-3.26)]. There is a need for strengthening health systems and addressing cultural factors that impede efforts at expanding coverage of malaria prevention strategies in Nigeria.